2016
DOI: 10.1002/elps.201500514
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and profiling of lyso‐phospholipids in fresh and in thermally stressed mussels by hydrophilic interaction liquid chromatography—electrospray ionization—Fourier transform mass spectrometry

Abstract: The separation efficiency of hydrophilic interaction liquid chromatography and the high resolution/accuracy of electrospray ionization-Fourier transform MS were successfully applied to the detailed characterization of lyso-phosphatidylcholines (LPCs) and lyso-phosphatidylethanolamines (LPEs) contained in the lipid extracts of Mytilus galloprovincialis (Mediterranean mussel). As a result, 57 LPCs, including regio- and positional isomers, and 45 LPEs, including acyl and plasma(e)nyl species, were identified. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 30 publications
13
47
0
Order By: Relevance
“…Such a process would imply the preliminary generation (catalyzed by endogenous phospholipases) of lyso ‐PL (ie PL missing one of their acyl chains), that would be subsequently converted, through esterification mediated by further enzymes, into new PL with appropriate side chains composition. A study recently performed in our laboratory on M galloprovincialis showed that refrigeration at 4°C of alive mussels for several days led to a progressive increase of the incidence of lyso forms of their major PL classes, namely, phosphatidylcholines (PC) and PE, with respect to their diacylic precursors . Actually, a not negligible presence of lyso ‐PL was also found in the case of gilthead sea bream ( Sparus aurata ) fillets subjected to low temperatures .…”
Section: Introductionsupporting
confidence: 86%
“…Such a process would imply the preliminary generation (catalyzed by endogenous phospholipases) of lyso ‐PL (ie PL missing one of their acyl chains), that would be subsequently converted, through esterification mediated by further enzymes, into new PL with appropriate side chains composition. A study recently performed in our laboratory on M galloprovincialis showed that refrigeration at 4°C of alive mussels for several days led to a progressive increase of the incidence of lyso forms of their major PL classes, namely, phosphatidylcholines (PC) and PE, with respect to their diacylic precursors . Actually, a not negligible presence of lyso ‐PL was also found in the case of gilthead sea bream ( Sparus aurata ) fillets subjected to low temperatures .…”
Section: Introductionsupporting
confidence: 86%
“…These findings are consistent with those inferred previously from the LPC/PC and LPE/PE concentration ratios (see Fig. 6 in ref …”
Section: Resultssupporting
confidence: 94%
“…, the presence of compounds bearing an additional OH group was inferred also in the case of CPE. Moreover, some accurate m/z values detected in the MS spectra of CPE and CAEP classes could be assigned to sodium adducts ([M + Na] + ), as already observed for lysophosholipids detected in the lipid extracts of mussels and gilthead sea breams . The perfect alignment found for peaks detected in the extracted ion current (XIC) chromatograms related to m/z ratios of proton and sodium adducts of the same CPE or CAEP species suggested that sodium adducts were formed during the ESI process.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations